2022
DOI: 10.1096/fasebj.2022.36.s1.0r781
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐(1‐7) Mas Receptors Localized to Proopiomelanocortin Neurons Tonically Regulate Insulin Sensitivity

Abstract: Angiotensin (Ang)‐(1‐7), a protective hormone of the renin‐angiotensin system, has emerged as a novel target to improve cardiovascular and metabolic functions in animal models. In addition to blood pressure lowering effects, recent studies from our laboratory and others have shown that Ang‐(1‐7) can promote insulin sensitization and weight loss in obese rodents. Our recent preliminary findings suggest these effects are centrally‐mediated, with Ang‐(1‐7) mas receptors (MasR) widely distributed to the arcuate nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…113 While we did not measure insulin sensitivity directly in this study; Mehay et al identified that Ang 1-7 can improve insulin resistance. 114 Given that decreasing peptidoglycan and systemic endotoxemia would reduce systemic inflammation and improve insulin resistance, 115 we would postulate that both cohorts with sustained ACE2 expression would have improved insulin sensitivity compared with control Akita mice contributing to the improved glucose homeostasis we observed. Future studies should extend these observations.…”
Section: Discussionmentioning
confidence: 99%
“…113 While we did not measure insulin sensitivity directly in this study; Mehay et al identified that Ang 1-7 can improve insulin resistance. 114 Given that decreasing peptidoglycan and systemic endotoxemia would reduce systemic inflammation and improve insulin resistance, 115 we would postulate that both cohorts with sustained ACE2 expression would have improved insulin sensitivity compared with control Akita mice contributing to the improved glucose homeostasis we observed. Future studies should extend these observations.…”
Section: Discussionmentioning
confidence: 99%